FTY720 promotes pulmonary fibrosis when administered during the remodelling phase following a bleomycin-induced lung injury. (June 2017) - Gendron, David R.; Lemay, Anne-Marie; Lecours, Pascale Blais; Perreault-Vallières, Valérie; Huppé, Carole-Ann; Bossé, Ynuk; Blanchet, Marie-Renée; Dion, Geneviève; Marsolais, David
Abstract: Fibrosis complicates numerous pathologies including interstitial lung diseases. Sphingosine analogs such as FTY720 can alleviate lung injury-induced fibrosis in murine models. Contradictorily, FTY720 also promotes in vitro processes normally leading to fibrosis and high doses in vivo foster lung fibrosis by enhancing vascular leakage into the lung. The goal of this study was to determine the effect of low doses of FTY720 on lung fibrosis triggered by an acute injury in mice. We first defined the time-boundaries delimiting the inflammatory and remodelling phases of an injury elicited by bleomycin based on neutrophil counts, total lung capacity and lung stiffness. Thereafter, FTY720 (0.1 mg/kg) was delivered during either the inflammatory or the remodelling phases of bleomycin-induced injury. While FTY720 decreased fibrosis by 60% and lung stiffness by 28% when administered during the inflammatory phase, it increased fibrosis (2.1-fold) and lung stiffness (1.7-fold) when administered during the remodelling phase. FTY720-induced worsening of fibrosis was associated with an increased expression of connective tissue growth factor, but not with vascular leakage into the lung. Thus, the timing of FTY720 delivery following a bleomycin-induced lung injury determines pro-vs anti-fibrotic outcomes.